2017
DOI: 10.3389/fmicb.2017.00609
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Structure of Escherichia coli Population and the Pattern of Virulence Genes along a Rural Aquatic Continuum

Abstract: The aim of this study was to investigate the diversity of the Escherichia coli population, focusing on the occurrence of pathogenic E. coli, in surface water draining a rural catchment. Two sampling campaigns were carried out in similar hydrological conditions (wet period, low flow) along a river continuum, characterized by two opposite density gradients of animals (cattle and wild animals) and human populations. While the abundance of E. coli slightly increased along the river continuum, the abundance of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 83 publications
10
32
1
1
Order By: Relevance
“…In the present study, we found evidence of a strong, positive association between ruminant FST markers (Rum2Bac) and eaeA-stx codetection, and between human FST markers (HF183) and Salmonella isolation. In general, these findings are consistent with past studies that found strong associations between ruminant fecal contamination and detection of pathogenic E. coli markers (Walters et al, 2007;Petit et al, 2017), and between human fecal contamination and Salmonella detection (Marti et al, 2013;Liang et al, 2015;Stea et al, 2015). For example, Stea et al (2015) found that the odds of detecting molecular makers for Salmonella in Nova Scotia surface water samples was 2.2 times greater when human FST markers were present as opposed to when human FST markers were not detected.…”
Section: Salmonella Isolation and Eaea-stx Codetection Were Associatesupporting
confidence: 90%
“…In the present study, we found evidence of a strong, positive association between ruminant FST markers (Rum2Bac) and eaeA-stx codetection, and between human FST markers (HF183) and Salmonella isolation. In general, these findings are consistent with past studies that found strong associations between ruminant fecal contamination and detection of pathogenic E. coli markers (Walters et al, 2007;Petit et al, 2017), and between human fecal contamination and Salmonella detection (Marti et al, 2013;Liang et al, 2015;Stea et al, 2015). For example, Stea et al (2015) found that the odds of detecting molecular makers for Salmonella in Nova Scotia surface water samples was 2.2 times greater when human FST markers were present as opposed to when human FST markers were not detected.…”
Section: Salmonella Isolation and Eaea-stx Codetection Were Associatesupporting
confidence: 90%
“…The prevalance of B1 and E, and some B2 in water, water plant and sediment was consistant with previous studies where B1 have been interpreted as generalists and harbor traits linked to plant association, whereas B2 strains are associated more with animals [53,54]. Phylogroup distribution within the E. coli population in both water and superficial sediments showed spatial variation [31]. It has also been reported that phylogenetic groups are adaptable and genotypically influenced by changes in environmental conditions, however phylogroup B1 isolates seem to persist in water [8,55].…”
Section: Discussionsupporting
confidence: 86%
“…This pond is located between the edge of town, a nature park, and a cattle pasture, and surrounded by dense scrub and trees, rarely visited by humans. Water (31), sediment (27), water plant (35), and snail samples (20) were collected from the pond, and bovine feces (7) was collected from the adjoining cattle pasture. Samples were placed into sterile 50 mL conical screw cap tubes, brought to the laboratory on ice and processed on the same day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural runoff into surface waters used for recreational activities and drinking water sources is a concern for watersheds around the world (Jokinen et al, 2012; Haack et al, 2015, 2016; Petit et al, 2017). Here, E. coli presence and elevated concentrations were significantly associated with the WR site, highlighting the potential impact of surface runoff from the upper portion of the WR dominated by hardwood forests (59%), pasture (30%), and cropland (9%) compared with just 4% urban land use (ANRC, 2012).…”
Section: Resultsmentioning
confidence: 99%